Lecture Notes Medical microbiology and infection - Elliott, Tom Casey, Anna (Lecture notes (Blackwell Publishing Ltd.), 2001)
Ideal for medical students and much more, this resource presents a thorough introduction and overview of medical microbiology and infection.